208k views
1 vote
What is the simplified form of the following expression?

What is the simplified form of the following expression?-example-1

1 Answer

1 vote

Answer:


\large\boxed{7\sqrt[3]{2x}-3\sqrt[3]{16x}-3\sqrt[3]{8x}=\sqrt[3]{2x}-6\sqrt[3]{x}}

Explanation:


7\sqrt[3]{2x}-3\sqrt[3]{16x}-3\sqrt[3]{8x}\\\\=7\sqrt[3]{2x}-3\sqrt[3]{(8)(2x)}-3\sqrt[3]{8x}\qquad\text{use}\ \sqrt[n]{ab}=\sqrt[n]{a}\cdot\sqrt[n]{b}\\\\=7\sqrt[3]{2x}-3\sqrt[3]8\cdot\sqrt[3]{2x}-3\sqrt[3]8\cdot\sqrt[3]{x}\\\\=7\sqrt[3]{2x}-3(2)\sqrt[3]{2x}-3(2)\sqrt[3]{x}\\\\=7\sqrt[3]{2x}-6\sqrt[3]{2x}-6\sqrt[3]{x}\\\\=\sqrt[3]{2x}-6\sqrt[3]{x}

User Oneklc
by
5.9k points